Factors Affecting the Converstion of Agricultural Land in Pandeglang Regency - Kusumastuti, Ayu Candra; M. Kolopaking, Lala; Barus, Baba (Sodality: Jurnal Sosiologi Pedesaan, 2018)
ABSTRACTIncreasing the number of people in Java affected the increasing demand for land for community activities. This became one of the drivers of the conversion of agricultural land into non-agricultural land. On the other hand, the increasing need for food makes the government must establish a policy of protection of agricultural land so as not to be converted. Efforts to control food land conversion need to look at the factors that affect land conversion in each region. Thus, the established program is more effective because it is able to answer the problems faced by the community, especially the land owner. This study aims to identify factors affecting land conversion in Pandeglang Regency. The factors was analyzed by ordinal regression.. The results showed that factors affecting land conversion are land tenure, B/C ratio of paddy farming, and road conditions. The effort to suppress the conversion of agricultural land requires the commitment of the government and the community as policy actors. The establishment of rural area institutions based on local community business is one solution to prevent the conversion of agricultural land.Keywords: Land conversion, food-crop land protection, rice field, institutionABSTRAKPeningkatan jumlah penduduk di Pulau Jawa berpengaruh pada peningkatan kebutuhan lahan untuk aktivitas masyarakat. Hal ini menjadi salah satu pendorong terjadinya alih fungsi lahan pertanian menjadi lahan non pertanian. Di sisi lain, kebutuhan pangan yang semakin meningkat membuat pemerintah harus menetapkan kebijakan perlindungan lahan pertanian pangan agar tidak dialih fungsikan. Upaya pengendalian alih fungsi lahan pangan perlu melihat faktor-faktor yang mempengaruhi alih fungsi lahan di masing-masing wilayah. Sehingga, program yang ditetapkan lebih efektif karena mampu menjawab permasalahan yang dihadapi masyarakat khususnya pemilik lahan. Penelitian ini bertujuan untuk mengidentifikasi faktor yang mempengaruhi alih fungsi lahan di Kabupaten Pandeglang dan. Faktor-faktor yang mempengaruhi alih fungsi lahan dianalisis dengan uji regresi ordinal. Hasil penelitian menunjukkan bahwa faktor yang mempengaruhi alih fungsi lahan adalah luas penguasaan lahan, B/C rasio usaha tani padi, dan kondisi jalan. Usaha menekan konversi lahan pangan memerlukan komitmen pemerintah dan masyarakat sebagai pelaku kebijakan. Pembentukan kelembagaan kawasan perdesaan berbasis bisnis komunitas lokal menjadi salah satu solusi dalam mencegah alih fungsi lahan pertanian pangan.Kata Kunci: alih fungsi lahan, perlindungan lahan pertanian pangan, sawah, kelembagaan